Drivers of local food consumption: a comparative study. Issue 9 (7th September 2015) - Bianchi, Constanza; Mortimer, Gary
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to empirically explore antecedents of local food purchase intention in two food producing countries with different cultural backgrounds. Design/methodology/approach – An online survey was employed to collect data from consumers located in Chile (n=283) and Australia (n=300). A proposed model is tested with structural equation modelling. Findings – Attitude towards consuming local food is a strong and direct driver of intentions to purchase local food in both countries. Attitude towards supporting local agri-businesses and consumer ethnocentrism are found to positively impact attitude towards consuming local food in both countries. Attitude towards local agri-businesses also has a direct effect on intentions to purchase local food in Australia, but not in Chile. Interestingly, subjective norms are not found to affect intentions to consume local food in either country. Research limitations/implications – The paper examines factors affecting the attitude towards and behavioural intention regarding local food consumption and develops an extended model of local food consumption. An outcome of this new model is the inclusion of personal variables, which influence local food purchasing behaviour. Practical implications – Producers and retailers need to develop campaigns explaining how consuming local food supports local businesses and farmers, which will reinforce personal values associated with local consumption. Originality/value – This is the first study to demonstrate that positive attitudes towards local foods are important drivers of local food purchase behaviour, independent of the cultural characteristics or level of economic development within a country.